1966
DOI: 10.1071/ar9660557
|View full text |Cite
|
Sign up to set email alerts
|

Vital statistics for an experimental flock of Merino sheep. III. Factors affecting wool and body characteristics, including the effect of age of ewe and its possible interaction with method of selection

Abstract: Estimates were made of the effects of the following factors on 10 fleece and body characteristics measured on breeding ewes aged 1½ to 10½ years in three mating groups over a period of 15 years: age of ewe, single or twin birth, age of dam, the ewe's own lambing performance, the year in which measurements were made, and the year in which each set of ewes was born. Two groups (S and MS) were under selection for high clean wool weight at 15–16 months, with a ceiling on wrinkle score and fibre diameter, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…This would be partly due to change in diameter being less easy to detect than changes in clean wool weight, for volume (weight, assuming density is constant) of wool is proportional to diameter 3 . It could also reflect a reduction in the number of active follicles (Brown et al 1966). There was no indication, however, that the reduction in wool growth during pregnancy was due to any factor other than decreased production per follicle.…”
Section: Discussionmentioning
confidence: 96%
“…This would be partly due to change in diameter being less easy to detect than changes in clean wool weight, for volume (weight, assuming density is constant) of wool is proportional to diameter 3 . It could also reflect a reduction in the number of active follicles (Brown et al 1966). There was no indication, however, that the reduction in wool growth during pregnancy was due to any factor other than decreased production per follicle.…”
Section: Discussionmentioning
confidence: 96%
“…The accepted view for Merino sheep is that as they increase in age fibre diameter (FD) increases and staple length (SL) decreases (Brown et al, 1966;Black and Reis, 1979;Hatcher et al, 2005). Such analyses did not determine if variations in liveweight were more important than age in determining FD as exemplified by the well documented effects of stocking rate on Merino wethers and ewes, where increases in liveweight with age may not occur at higher stocking rates and FD may not change (e.g.…”
Section: Change With Liveweight and Animal Sizementioning
confidence: 97%
“…Jackson et al (1975) reported negative phenotypic and genetic correlations between follicle measurements (number of follicles and S:P ratio) and mean fibre diameter to 15-16 months of age in Merino sheep, and that both follicle characteristics explained a major portion of the genetic variation in clean wool weight. With respect to the effect of birthrank on wool production, it is often observed that twin-born animals produce about 4% less wool which is up to 0.2 p m broader than contemporary single-born animals (Turner 1961;Brown et al 1966;Turner et al 1968;File 1981).…”
Section: Introductionmentioning
confidence: 98%